Assessment of functional capacity in patients attending geriatrics outpatient department at Civil Hospital, Ahmedabad - Neeta Mathur (Wolters Kluwer Medknow Publications, 2016)
Aims: To access the quality of life in terms of functional capacity and to estimate the prevalence of depression among geriatric patients. Settings and Design: A hospital-based study was conducted in Civil Hospital, Ahmedabad between July and September 2006. The patients aged 65 years and above were included in the geriatrics outpatient department. Methods: The geriatric patients were interviewed during their geriatric clinic visit using a structured questionnaire regarding instrumental activities of daily living (IADL), basic activities of daily living (ADL), Nagi physical disability scale, and short version of the geriatric depression scale. Statistical Analysis Used: Data were analyzed using EPI-Info Statistical Packages. Using a scoring system, mean, standard deviation, and the significance of the results was tested using the Chi-square test and Z-test was used to compare quantitative data. Results: Mean IADL score of males is 4.05 whereas of females is 2.91 which is significant (P < 0.05). Overall scores for ADL showed no statistically significant results between male and female geriatric subjects. The mean scores of restriction of basic activities on the Nagi scale of physical disability were not significant among women. Mean scores of depression were highly significant in IADL, basic ADL, and limitation of basic movement while significant in a greater number of reported symptoms. Conclusions: Depression was due to combined effect of increased scores of IADL, ADL, and Nagi physical disability scale.